Sketchfab Augmented Interactive 3D Media Drives Learning Interest and Understanding in Elementary Mathematics: Media 3D Interaktif Berbasis Sketchfab Mendorong Minat Belajar dan Pemahaman Matematika Sekolah Dasar - Trisia, Dina; Ninawati, Mimin (Academia Open, 2026)
General Background Digital educational transitions increasingly mandate interactive visual technologies to secure elementary student engagement and sustained pedagogical development. Specific Background Teaching abstract mathematical concepts, such as simple fractions, relies heavily on these visual media tools to translate complex ideas into concrete, comprehensible formats for young learners. Knowledge Gap Although virtual reality and 3D modeling have advanced considerably, there is a distinct lack of research explicitly developing and testing accessible platforms like Sketchfab to elevate affective learning domains, specifically students' learning interest toward abstract fractions. Aims This study designs and evaluates a Sketchfab-based interactive 3D visual medium targeting the enhancement of fourth-grade students' learning interest and academic achievement in simple fractions. Results Utilizing the ADDIE framework across experimental and control groups at SDN Susukan 07 Pagi, the developed media achieved a "very feasible" expert validation rating. Quantitative assessments revealed a significant experimental achievement increase (Sig. = 0.000), a moderate N-Gain (0.31), a very strong Cohen's d effect size (2.285), and an average learning interest score reaching 82.29%. Novelty This study distinctively positions Sketchfab not merely as a visualization tool, but integrates it conceptually with cognitive load reduction theories to intentionally drive both cognitive achievement and affective learning interest. Implications Elementary educators should integrate interactive 3D platforms within their curricula, utilizing structured worksheets and guided exploration, to concretize abstract mathematical principles and actively sustain student engagement. Highlights Interactive 3D visualization significantly reduces cognitive abstraction when learning simple fractions. The Sketchfab platform successfully elevates both mathematical achievement and affective learning interest. Expert validation confirms the very high feasibility of these developed digital instructional designs. Keywords Interactive Learning Media; Sketchfab; Elementary Mathematics; Learning Interest; ADDIE Model